Cytology meets next generation sequencing and liquid biopsy: A case of lung adenocarcinoma presenting as metastasis to the phalanx. Issue 8 (22nd April 2020) - Clery, Eduardo; Pisapia, Pasquale; Migliatico, Ilaria; Pepe, Francesco; De Luca, Caterina; Russo, Maria; De Rosa, Filippo; Smeraglia, Francesco; Insabato, Luigi; Vigliar, Elena; Malapelle, Umberto; Mariconda, Massimo; et al.
Abstract: Carcinomas do rarely metastasize to the finger. Non‐small‐cell lung cancer is most frequently involved. To date, only a few cases have been reported, on histology. Here we describe the cytological features of a metastatic lung adenocarcinoma case to the phalanx of the right forefinger as initial manifestation of the neoplastic disease in a 69‐years‐old woman. The cytological microscopic findings, complemented by a wide array of ancillary techniques, were confirmed by histology. Neoplastic cells were positive for cytokeratin 7 (CK7) and thyroid transcription factor 1 (TTF‐1), harboring, in tissue and in bloodstream samples, an uncommon epidermal growth factor receptor ( EGFR ) exon 20 p.S768_D760DUP, detected by next generation sequencing (NGS) and liquid biopsy. Cytology corroborated by immunocytochemistry, NGS, and liquid biopsy is a modern approach to provide diagnostic and therapeutic information even in rare and challenging cases.